The Ati-Atihan Festival: Its Impact to the Economy and Tourism Industry in Kalibo, Aklan - Calopez, Christopher G.; Gaas, Charlotte; Lleva, Gilbert; Maneclang, Diana Rose; Fusin, Dennis (JPAIR Multidisciplinary Research, 2011)
Ati-Atihan is a feast held annually in honor of the Senior Sto. Niño concluding on the third Sunday of January in the town of Kalibo, Aklan .The study aimed at assessing the economic and tourism impact of the Ati-Atihan Festival to the Municipality of Kalibo, Aklan. This descriptive study involved 120 respondents composed of residents, businessmen and local government officials who were selected using the purposive sampling method. A one-shot survey was conducted to gather pertinent data and treated using descriptive and inferential statistics. Results revealed that respondents believed that the Ati-Atihan festival had an impact on the economy of the town by bringing about the expansion and improvement of local products and in increasing the economic activity in the town. It had an impact on the tourism industry by attracting tourists both locally and internationally. However, significant differences were found concerning the impact of Ati-Atihan festival. Thus, certain recommendations were formulated for the enhancement of the celebration as well as to boost the tourism industry and the economy of the municipality.